Распространение и экологические особенности некоторых Cladocera в субарктических водоемах Европейской части СССР - Вeхов, H.B. (Вестник зоологии, 1982)
Summer temperature, thickness of winter frozen layer of water and presence or absence of macrophytes are suggested to be essential factors of copepods distribution over Subarctic water bodies. Southern woodland species (Limnosida frontosa, Diaphanosome brachyurum, Leptodora kinndti) scarcely occur in Subarctics, they are characteristic with low population level and fertility. The Northern complex copepods (Bythotrepheslongi- manus, Polyphemus pediculus, Holopedium gibberum) are widely distributedin Subarc- tic water bodies and characterized by high abundance and fertility. Under Subarctic con- ditions both groups show faster development, body growth and earlier maturity than in middle area.